The differences in level of trait anxiety among girls and boys aged 13–17 years with myopia and emmetropia. Issue 1 (December 2016) - Łazarczyk, Joanna; Urban, Beata; Konarzewska, Beata; Szulc, Agata; Bakunowicz-Łazarczyk, Alina; Żmudzka, Ewa; Kowzan, Urszula; Waszkiewicz, Napoleon; Juszczyk-Zajkowska, Karolina
Abstract Background A significant increase in myopia among children and teenagers can be observed all over the world. Yet at the same time, there is still an insignificant number of studies concerning this health problem. The aim of this study was to assess the level of trait anxiety among myopic group of teenagers in comparison to teenagers with emmetropia, and to confirm whether the level of trait anxiety relates to age and gender. Methods Two hundred thirty-nine students aged 13–17 years were included in the study. The study group comprised 114 persons with myopia (81 girls and 33 boys), while the control group comprised 125 persons without refractive error (79 girls and 46 boys). Volunteers completed a set of questionnaires including: personal data, State-Trait Anxiety Inventory for Children (STAIC) (13–14 year-olds), or State-Trait Anxiety Inventory (STAI) (15–17 year-olds). The trait anxiety subscales were thus analyzed. Results Among younger adolescents (13–14 years of age) with myopia there was a significantly higher incidence of pathological intensification of anxiety as a constant trait. After taking into account the distribution of gender, there was a higher level of trait anxiety in the group of boys with myopia than in the control group aged 13–17 years and 13–14 years. There was also a higher level of trait anxiety detected in males than in females. Conclusions Myopia may affect the level of trait anxiety among 13–14-year-olds. In both age groups of girls, a higher percentage of patients with high level of anxiety was discovered (≥7 sten), as compared to their peers without vision defects. Our results can contribute to a more accurate analysis of young teenagers' psychological problems, especially among boys diagnosed with myopia.